Efficient naphthenic acid extraction from high acidic oil using novel 1, 5-diazabicyclo[4.3.0]non-5-ene based ionic liquids. (15th December 2021) - Su, Tiezhu; Li, Yin; Yan, Qingdian; Zhang, Xinyi; Lin, Haichen; Yang, Shuliang; Su, Peifeng; Wang, Hongtao; Su, Yuzhong; Hong, Yanzhen; Peng, Li; Li, Jun
Abstract: In this work, the high acidic crude oil deacidification study was performed with novel 1-alkyl-1, 5-diazabicyclo[4.3.0]non-5-ene (DBN) based ionic liquids (ILs). Firstly, we took advantage of the systematic COSMO-RS (Conductor-like Screening Model for Real Solvents) calculations to screen the possible ILs with good acid extraction performance from the combinations of 94 cations and 56 anions. Four 1-alkyl-1, 5-diazabicyclo[4.3.0]non-5-enium imidazolide ([DBN-R][IM]) ILs with varying alkyl chains were eventually identified and synthesized successfully. Their deacidification performances were tested experimentally and different factors, including the alkyl chain length, ILs/oil mass ratio, temperature, and the initial total acid number (TAN) value of the simulated acidic oil, were also studied in detail. The experimental results showed that [DBN-R][IM] exhibited excellent performances on naphthenic acids (NAs) removal and [DBN-Et][IM] could achieve 93% of NAs removal employing the ILs/oil mass ratio of 0.06 at room temperature for the acidic oil with the TAN value of 3.28 mg KOH/g. COSMO-RS analyses were also used to elucidate the unusual effects of the alkyl chain length and temperature on the NAs extraction performances. Additionally, a two-step deacidification strategy was proposed aiming at realizing more efficient NAs extraction. Finally, density functional theory (DFT) calculations were carried out and the independent gradient model (IGM) analyses were applied to the IL-NAs system to get insight into the deacidification mechanism of the ILs. Graphical abstract: Image 1 Highlights: Four ionic liquids were screened out theoretically from 5264 ionic liquids for naphthenic acids extraction. Four novel 1, 5-diazabicyclo[4.3.0]non-5-ene based ionic liquids were synthesized successfully. Deacidification factors were experimentally investigated and analyzed theoretically. A two-step deacidification strategy was proposed. DFT calculations and independent gradient model analyses were performed to study the mechanism.